A proposed guidance and counseling program for the novitiate of the Congregation of Mother of Carmel in Kerala, India - Philositta, Achamma J. (Animo Repository, 1979)
This study surveys the problems and needs of the novices of the Congregation of Mother of Carmel (C.M.C.) in Kerala, India through the problem checklist and questionnaire and proposed an organized guidance program based on their needs. The study made use of the descriptive research survey. All the 50 novices of the congregation of Mother of Carmel in Kerala with an age range of 18 to 28 were the subjects of the study. The subjects also included the six staff members of the novitiate whose age range was from 30 to 58. From this study, the following conclusions are drawn: 1. As revealed by the problem checklist, the novices face different kinds of problems such as personal, psychological relations, leisure and recreation, health, spiritual development and sex. 2. The present formation program meets, to some extent, some of the needs of the novices. However, they can be better organized and modified based on the answers of the questionnaire. 3. There is an openness on the part of the novices in discussing personal matters with the formation personnel. This could pave the way for better utilization of the counseling service. 4. The staff members as well as the novices are in favour of the establishment of a guidance program. 5. There are several formational activities that could be incorporated into the proposed guidance program. There is a service that takes care of the individual data, their biographical and health data. This service could be utilized in the establishment of the Individual Inventory Service. Orientation programs and camps are also conducted every year and it could be used in the orientation program. They are also provided with information about their vocation and spirituality and this could be incorporated in the Information Service. Spiritual direction and individual consultations will be integrated in the counseling service. 6. A guidance program which embodies the philosophy and objectives of the formation is proposed. This program recommended the following guidance services in order to meet t